2010
DOI: 10.1542/peds.2009-3239
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Admissions for Pediatric Status Asthmaticus in New Jersey Over a 15-Year Period

Abstract: Although fewer children are being admitted with status asthmaticus, the proportion of patients managed in PICUs is climbing. There has been no substantial change in rates of mechanical ventilation or death. Additional research is needed to better understand how patients and physicians decide on the appropriate site for hospital care and how that choice affects outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 35 publications
7
55
3
Order By: Relevance
“…22 Another analysis of an administrative database (New Jersey State Inpatient Database) reported an increase in the proportion of children admitted to the ICU during the last 2 decades: from 3% in 1990 to 20% in 2006. 4 Likewise, our recent analysis of nationally representative data of pediatric hospitalizations (Kids' Inpatient Database) also revealed a 28% increase in the use of mechanical ventilation in children hospitalized for asthma exacerbation between 2000 and 2009. 3 Although inferences from the administrative data are somewhat limited because of potential error in data collection and coding, the current study involving 14 hospitals across 12 states revealed that 34% of children hospitalized with asthma exacerbation were admitted to the ICU during 2012 to 2013.…”
Section: Substantial Burden Of Children Admitted To the Icumentioning
confidence: 94%
See 1 more Smart Citation
“…22 Another analysis of an administrative database (New Jersey State Inpatient Database) reported an increase in the proportion of children admitted to the ICU during the last 2 decades: from 3% in 1990 to 20% in 2006. 4 Likewise, our recent analysis of nationally representative data of pediatric hospitalizations (Kids' Inpatient Database) also revealed a 28% increase in the use of mechanical ventilation in children hospitalized for asthma exacerbation between 2000 and 2009. 3 Although inferences from the administrative data are somewhat limited because of potential error in data collection and coding, the current study involving 14 hospitals across 12 states revealed that 34% of children hospitalized with asthma exacerbation were admitted to the ICU during 2012 to 2013.…”
Section: Substantial Burden Of Children Admitted To the Icumentioning
confidence: 94%
“…3 Parallel to the increasing asthma prevalence in children, an analysis of administrative claims data from New Jersey reported a 6-fold increase in the use of intensive care units (ICUs) in children with asthma exacerbations between 1992 and 2006. 4 However, given the inevitable questions about generalizability (eg, single state data from >8 years ago), along with potential errors in data collection and coding in claims data, the burden of ICU admission for children with asthma exacerbation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…13 The burden of asthma includes lost work for parents and school for children, [14][15][16] lower quality of life, 16,17 increased emergency department (ED) visits and hospitalizations, 18 and death. 19 In addition, our previous research suggests that families of US children with asthma who are able to actively communicate with clinicians from home are far more likely to report high levels of SDM, 20 and that this process also may be associated with improved health and lower health care costs. 21 In this study, our objective was to test the feasibility, acceptability, and impact of an innovative, EHR-linked patient portal with decision support directed at both families and clinicians on asthma outcomes.…”
Section: What This Study Addsmentioning
confidence: 99%
“…A recent study by Hartman et al may lend credibility to this theory. 10 They examined administrative data from New Jersey and concluded that, while fewer children were admitted with status asthmaticus, the proportion of patients managed in pediatric intensive care units (ICUs) was climbing, despite no substantial rate increases in mechanical ventilation or death.…”
Section: Epidemiology Of Asthmamentioning
confidence: 99%
“…Additional research is necessary to better comprehend how patients and physicians decide on the appropriate site for hospital care and how that choice affects outcome. 96 …”
Section: Acute and Ambulatory Care Management Emergency Department Trmentioning
confidence: 99%